A review of the representation of PIRLS related research in scientific journals. (October 2015) - Lenkeit, Jenny; Chan, Jessica; Hopfenbeck, Therese N.; Baird, Jo-Anne
Abstract: Recent decades have seen a rise of international large-scale assessments, which have become an influential instrument for informing educational policies. Likewise, they play an ever-increasing role in academic research. The vast information provided by the surveys relate to research topics relevant in various disciplines. We review the impact of the Progress in International Reading Literacy Study (PIRLS) on academic research and its representation in English language peer reviewed journals. Five literature bases were exploited for the bibliography and strict inclusion criteria set. Articles were analysed according to a comprehensive coding scheme and the resulting data was analysed with SPSS. Results map the evolution of PIRLS related research from the study's beginning, across geographic regions and disciplines. They describe types of research conducted and identify the most commonly investigated topics. Findings point towards topics that have so far been neglected, but would make valuable contributions to the research field. Highlights: 114 peer-reviewed, English-language, PIRLS related research articles were identified. Germany and the United States published most articles. PIRLS is mostly used for secondary data analysis. PIRLS is hardly used for reading research, despite being a reading survey. Some topics within the study remain virtually untouched by research.